Endemic Lineages of Batrachochytrium dendrobatidis Are Associated With Reduced Chytridiomycosis-Induced Mortality in Amphibians: Evidence From a Meta-Analysis of Experimental Infection Studies - Belasen, Anat M.; Russell, Imani D.; Zamudio, Kelly R.; Bletz, Molly C. (Frontiers in Veterinary Science, 2022)
Emerging infectious wildlife diseases have caused devastating declines, particularly when pathogens have been introduced in naïve host populations. The outcome of disease emergence in any host population will be dictated by a series of factors including pathogen virulence, host susceptibility, and prior opportunity for coevolution between hosts and pathogens. Historical coevolution can lead to increased resistance in hosts and/or reduced virulence in endemic pathogens that allows stable persistence of host and pathogen populations. Adaptive coevolution may also occur on relatively short time scales following introduction of a novel pathogen. Here, we performed a meta-analysis of multi-strain Batrachochytrium dendrobatidis (Bd) infection experiments to test whether: (1) amphibian hosts exhibit lower mortality rates when infected with strains belonging to endemic Bd lineages relative to the Global Panzootic Lineage (Bd-GPL), hypothetically owing to long co-evolutionary histories between endemic Bd lineages and their amphibian hosts; and (2) amphibians exhibit lower mortality rates when infected with local Bd-GPL strains compared with non-local Bd-GPL strains, hypothetically owing to recent selection for tolerance or resistance to local Bd-GPL strains. We found that in a majority of cases, amphibians in endemic Bd treatments experienced reduced mortality relative to those in Bd-GPL treatments. Hosts presumed to have historically coexisted with endemic Bd did not show reduced mortality to Bd-GPL compared with hosts that have not historically coexisted with endemic Bd. Finally, we detected no overall difference in amphibian mortality between local and non-local Bd-GPL treatments. Taken together, our results suggest that long-term historical coexistence is associated with less disease-induced mortality potentially due to hypovirulence in endemic Bd lineages, and that more recent coexistence between amphibians and Bd-GPL has not yet resulted in reduced host susceptibility or pathogen virulence. This corroborates previous findings that Bd-GPL introduced via the global amphibian trade has a high capacity for causing disease-induced mortality.